Studi karakteristik asap cair oli bekas melalui proses steam reforming menggunakan katalis KOH - Anam, K.; Qiram, I.; Anas, M. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2022)
Waste oil has a high hydrogen content and can be used as renewable energy. The hydrocarbon chains in used oil can decompose and produce liquid fuel products through evaporation at a certain temperature. The purpose of this study was to obtain the characteristics of used oil waste liquid smoke using steam reforming with the addition of a KOH catalyst. The research was conducted by experiment, where the concentration of the solution used included 1.25; 1.66, and 2.5 Mol. The steam reforming process was carried out for 2 hours using a temperature variation of 250 and 300 oC. The steamer tube is connected to the condensing pipe in a separate unit to obtain liquid smoke products from a wide variety of applied solutions. Product analysis includes volume capacity and flame characteristics of each product variation obtained using the ImageJ application. The results showed that the role of KOH catalyst was able to increase the effectiveness of liquid smoke production from waste oil. The highest product volume was obtained at a concentration of 1.25 Mol of 115 ml. While the characteristics of the flame tend towards temperature and color dominance that is different for each product produced.